Shaklee vitamin C supplement / Tryphosa Faith Tueng - Tueng, Tryphosa Faith (2022)
I was given a task of running a business as a part of my assignment project. The purpose of this project or this business opportunity is to experience what and how it is like to be an entrepreneur. As a result, I decided to be an agent of supplement which is SHAKLEE Vitamin C. I come across an opportunity to be an agent of SHAKLEE with registration fees of RM5 only. Then, the modal to start this business is RM367.20. For business start-ups with this modal, I was bought 10 bottles of supplements Shaklee Vitamin C. Next is, I was promoting the supplement SHAKLEE Vitamin C via Instagram and WhatsApp status to find my customers. The duration of the project lasted for one month only. The project needs to be submitted on week 10 which is on 17 Jun 2022. So, I keep promote this supplement SHAKLEE to attract customers towards health so that they are healthier and more beautiful. I learnt something new and that is how to develop my self-image, improve my confidence and obtain new skills. Last but not least, during this period of business, I really grateful to meet good and friendly leaders of Shaklee and also helped me a lot in terms of how to serve customers and promote goods.